UPAYA PENCEGAHAN KORUPSI DI LINGKUNGAN SEKOLAH MELALUI PENANAMAN NILAI ANTI KORUPSI DI SDIT IZZATUL ISLAM KARAWANG - Safana H Hamidah; Rima Mulhimawati; Sabrina Septiani; Rifani Alina Syamsi; Nabilah Zalfaa; Nur Rachman Ramadhan; Muhammad Aly Fadhilah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Corruption is a moral and social problem that can be prevented through early education. This study aims to describe efforts to prevent corruption in schools by instilling anti-corruption values. This study employs a descriptive qualitative approach with data collection techniques consisting of interviews with teachers at the school. The results indicate that the school has implemented rules to prevent dishonesty and instilled values of honesty, trustworthiness, responsibility, and teacher role modelling in daily life. The strategies implemented include habit formation, emotional and rational approaches, setting a good example, and supporting activities such as an “honesty canteen” and character-building programs. Instilling anti-corruption values serves as a preventive measure in shaping students with integrity and moral awareness from an early age.